The effect of Combined chemical and mechanical pretreatment of poultry litter on the biogas productivity (Journal of Hama University, 2022)
Anaerobic digestion for organic wastes is one promising option in processing these waste. Poultry litter is considered as one of the organic waste in Syria, which can be a source of clean energy if treated anaerobically. This research  aimed to study the effect of combined chemical treatment (by adding 2%, 5%, 8% NaOH to the substrates)  and mechanical treatment (by milling substrates into 1, 3 and 10mm diameters pieces) pretreatment of these wastes on producing biogas and methane.  The batch experiences were conducted in laboratory of anaerobic digestion unit which consists of four digesters (13.5 L capacity each) at 37°C temperature, for 42 days. The results showed that combined pretreatment by milling the substrates into 1mm and adding 8%NaOH registered the best results of all kinds of pretreatment, followed by (without significantly differences) combined pretreatment by milling substrates into 1mm diameter pieces and adding 5%NaOH with a rate of increasing biogas productivity 108.48%, 106.15% respectively.
Keywords: Sodium hydroxide; poultry litter; biogas; methane; combined pretreatment